Implementation of Sustainable Slum Handling Program (Empirical Study of the KOTAKU Program) - Pratama, Alamsyah; Jamil, M. H.; Barkey, A. Roland (Department of Urban and Regional Planning, Universitas Diponegoro, 2021)
The handling of slums is an issue that continues to be a concern until now to realize a city and settlements are livable, inclusive, safe, and sustainable. To realize this, the Government & NUSP-2 collaborated to form the KOTAKU (City Without Slums) program. Sinjai Regency, South Sulawesi. This research used descriptive qualitative methods with logic analysis approaches, including data collection, reduction, display, and verification. Data collection used observation of slums that have been handled, documentation, and interviews with key informants. The results showed that the implementation of the KOTAKU program succeeded in reducing the area of slums in some priority areas of handling. The results also showed that not all aspects are sustainable applied to handling slums through the KOTAKU program.